KEMITRAAN MASYARAKAT BAGI PENGEMBANGAN USAHA ABON IKAN LELE BAGI KELOMPOK USAHA PKK KELURAHAN PLAJU DARAT KECAMATAN PLAJU KOTA PALEMBANG - Ade Vera Yani; Dasir Dasir; Inneke Abdillah Fahmi (Altifani Journal: International Journal of Community Engagement, 2025)
The PKK business group of Plaju Darat Village, as a partner in Community Service Activities has produced catfish floss but the quality is still low. Based on the initial moisture content of 4.10% and the initial oil content of 33.76% which causes the product to not last, the problems faced by partners are (1) lack of production tools (2) marketing is still done directly to consumers, (3) packaging is still simple (4) not doing business bookkeeping. The purpose of the community service activities is to improve the quality of catfish floss products and improve product marketing and financial management. The methods used are initial surveys, data collection of partner problems, training, counseling, providing tools and assistance in using fish meat presses, oil presses and bookkeeping as well as providing financial administration books. Another activity result was the addition of production equipment to the partner (in the form of a water press, spinner, vacuum sealer, and equipment for the fish floss production process). The partner has implemented online marketing and has maintained accounting records for the fish floss production business. Overall, the activity results achieved nearly 100% of the resolution of all the problems faced by the partner.